Strategi Pengembangan Agribisnis Hama Ulat Sutera Emas (Circula trifenestrata Helf.) (Lepidoptera:Saturniidae) pada Alpukat sebagai Pengembangan Potensi Desa di Desa Sidomulyo Kec. Silo Kab. Jember - Najmi Indah Indah (Jurnal Ilmiah Inovasi, 2017)
Circula trifenestrata is a kind of golden silkworms that are native wild habitat tropical areas like Indonesia. This gold silkworm living on host plants such as cashew nut, avocado, cocoa, soursop, mango, quinine and kedondong. Sidomulyo is largest coffee producer in Jember, and avocado crops are very abundant population because these plants shade the coffee plants. People assume that this type of worm that attacked the plant avocado is a kind of pest caterpillars can spend the leaves quickly and reduce the productivity of harvesting the fruit so that the caterpillars are often exterminated by farmers. The purpose of this study was to determine the outlook and development strategy pests into gold silk as potential Kab.Jember Sidomulyo village. Respondents who used an avocado farmer in the village of Sidomulyo, using analysis of FFA (Force Field Analysis) that identify factors driving and inhibiting factors in an activity will be achieved. The results showed the total value of the park on the driving factor is equal to 1.59 (D2 silkworm cocoon abundance of gold in avocados) while the number of inhibiting factors in the amount of 1.40 (H4 has been no development of silkworm farming gold in Kab.Jember). It shows that the value of the driving factors is greater than the value of the park in an inhibiting factor. Therefore, the cultivation of silkworms in Jember has the advantage to improve the prospects and potential development of silkworm gold C.trifenestrata in Jember.Â Keywords: Circula trifenestrata, silkworms gold, avocado, potential village